The novels of Fernando del Paso - Fiddian, Robin W. (University Press of Florida, 2000)
''Provides the reader with a clear understanding of art in general, and prose fiction in particular, in Mexico and the Western world in our century. [The authors] commentaries on the modern and the postmodern are insightful, refreshing, and informative.